Marketing of tourist areas in creating of attractive image of the region - Кожамкулова, Ж. (Journal of Economic Research & Business Administration, 2017)
Theoretical and practical aspects of marketing of tourist areas were examined in this article. Also different points of view the content of territorial marketing basics were explored. Through the prism of the consideration of territorial marketing we based the understanding of marketing of tourist areas, as a special type of marketing, with its inherent purpose, objectives, subject of research facilities and development actors. The development potential of the tourist market in the Republic of Kazakhstan, cultural and historical values of the country was examined in the article. There were considered the need to develop the marketing of tourist areas in the country, designed to ensure and enhance the image and attractiveness of a particular locality. As the implementation of the approach there were proposed the introduction and development of tourist areas of marketing process in the activities of the various objects, in particular in the organization of tourism of the Republic of Kazakhstan.